Dakwah Multikultural, Toleransi Beragama dan Forum Kerukunan Umat Bergama (FKUB) di Kota Medan - Muhammad Aidil Pratama; Faridah (Indonesian Journal of Humanities and Social Sciences, 2024)
This research investigates the role of multicultural da'wah in promoting religious tolerance through the Religious Harmony Forum (FKUB) in Medan City. Amidst significant ethnic and religious diversity, FKUB plays a crucial role in facilitating interfaith dialogue and preventing potential conflicts. The study employs a qualitative approach, utilizing in-depth interviews and participatory observations of FKUB members and the Medan community. The findings demonstrate that FKUB's multicultural preaching effectively fosters understanding and respect for religious differences. In Medan City, FKUB's efforts have successfully created an environment supportive of tolerance and respect for religious diversity. This achievement is evidenced by the Religious Piety Index rising from 82.52 in 2020 to 83.92 in 2021, and a harmony index of 76.3 in 2023, surpassing the national average of 73.83. Through an inclusive approach, active participation, and educational initiatives, FKUB significantly contributes to shaping an inclusive and harmonious society. These findings lay a crucial foundation for developing multicultural proselytization strategies in other communities aiming to achieve similar goals.